2019
DOI: 10.3389/fphys.2019.00806
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Cognitive Function During a Short Stay at Hypobaric Hypoxia Chamber (Altitude: 3842 M)

Abstract: Objective To observe the effects of a fast-acute ascent to high altitude on brain cognitive function and transcranial doppler parameters in order to understand the physiological countermeasures of hypoxia. Methods 17 high-altitude-naïve male subjects (mean age was 26.3 ± 8.1 years) participated in the study. We measured Critical Flicker Fusion Frequency (CFFF), blood oxygen saturation, Psychology Experiment Building (PEBL) including three tests (Modified Math Processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
1
15
1
Order By: Relevance
“…Our study showed preserved psychomotor vigilance after HH exposure in line with the results of other studies performed below 4,000 m ( Thomas et al, 2007 ; De Bels et al, 2019 ; Heinrich et al, 2019 ) but is in contrast with those performed above 4,000 m ( Roach et al, 2014 ; Davranche et al, 2016 ; Pun et al, 2018 ). However, more false starts at the PVT were observed in individuals with a worse sleep quality measured with the ISI after the first night at altitude (ISI > 7).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed preserved psychomotor vigilance after HH exposure in line with the results of other studies performed below 4,000 m ( Thomas et al, 2007 ; De Bels et al, 2019 ; Heinrich et al, 2019 ) but is in contrast with those performed above 4,000 m ( Roach et al, 2014 ; Davranche et al, 2016 ; Pun et al, 2018 ). However, more false starts at the PVT were observed in individuals with a worse sleep quality measured with the ISI after the first night at altitude (ISI > 7).…”
Section: Discussionsupporting
confidence: 92%
“…In the 18 included studies the fraction of inspired oxygen ranged from 10 to 18%. Differences in altitude-exposure speed, duration and profile, the way of ascent, study population, cognitive tests employed, and test administration times at altitude ( Li et al, 2000 ; Pavlicek et al, 2005 ; De Bels et al, 2019 ; Loprinzi et al, 2019 ) can explain discrepancies and hinder the drawing of conclusions regarding the effects of altitude on the cognition of recreationists.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in astronauts (Basner et al, 2015), aircraft pilots (Asmaro et al, 2013;Bustamante-Sánchez et al, 2019;Legg et al, 2012) and military helicopter pilots (Bouak et al, 2018;Legg et al, 2016) have explored the influence of HH on multiple cognitive domains but the precise effects on cognition are still unclear (Jung et al, 2020;McMorris et al, 2017). Contradictory results have been reported in different studies (De Bels et al, 2019;Li et al, 2000;Loprinzi et al, 2019;McMorris et al, 2011;McMorris & Hale, 2012;Pavlicek et al, 2015;Taylor et al, 2016), especially at moderate altitude. Some studies have reported reduced psychomotor vigilance (i.e., slowing of reaction time, RT) after exposure to reduced oxygen availability (altitude between 4350 and 5260 m above sea level (asl)) (Davranche et al, 2016;Pun et al, 2018;Roach et al, 2014) while others reported no effects (altitude between 1630 to 3962 m asl) (De Bels et al, 2019;Heinrich et al, 2019;Latshang et al, 2013;Thomas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, after exhaustion in the endurance task under hypoxia, the DLPFC tDCS condition had a significantly shorter CRT compared to sham. Recent studies have found mixed results regarding cognitive function while exercising in hypoxia, emphasizing that we are dealing with a more complex scenario than in normoxia [ 30 , 50 52 ]. It has been demonstrated that cognitive function is compromised as hypoxia severity increases, most likely due to hypoxia-induced impairment in neurovascular coupling, which is the primary mechanism of brain O 2 delivery [ 30 , 36 , 53 ].…”
Section: Discussionmentioning
confidence: 99%